2014
DOI: 10.1016/j.envsci.2014.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Our common future? Cross-scalar scenario analysis for social–ecological sustainability of the Guiana Shield, South America

Abstract: AcknowledgementsWe would like to thank all the participants of the North Rupununi and Guyana scenario workshops and Dominique Laffly for his advice in carrying out statistical analysis. Thank you to the anonymous reviewers for their comments. This research has been funded by the Environment Programme, Management of Natural Resources, DG Research and Innovation, European Commission 7 th Framework. 2 AbstractScenarios help build a shared understanding of potential futures and allow us to engage with how interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 42 publications
(41 reference statements)
2
22
0
Order By: Relevance
“…These themes are broadly consistent with those found from the local level of the scenario analysis conducted by Mistry et al (2014) in Guyana. However, in the case studies presented here, the diversity of socio-ecological contexts also identified important context-specific responses.…”
Section: Innovation In Response Options and Application Of Learning Csupporting
confidence: 76%
See 3 more Smart Citations
“…These themes are broadly consistent with those found from the local level of the scenario analysis conducted by Mistry et al (2014) in Guyana. However, in the case studies presented here, the diversity of socio-ecological contexts also identified important context-specific responses.…”
Section: Innovation In Response Options and Application Of Learning Csupporting
confidence: 76%
“…The opportunity for iterative refinement of response options based on the local context was considered by participants to be particularly effective in translating the results into implementation actions, supporting the findings of Mistry et al (2014) that scenarios at a local level can become more action-focussed than at higher levels of scale. Iteration was believed to improve communication channels between the community, external stakeholders and scientists, gradually bringing together disparate perspectives.…”
Section: Lessons For Community Scenario Planningsupporting
confidence: 55%
See 2 more Smart Citations
“…Guiana Shield, South America, and for determining the most effective and efficient use of emerging funding streams in order to promote social justice and ecological sustainability. We worked in four stages: Stage 1: Developing a shared cross-scalar and interdisciplinary understanding of the factors that may influence community social-ecological survival (see Berardi et al 2012Berardi et al , 2013aBerardi et al , b, 2015; Stage 2: Exploring future scenarios affecting social-ecological resilience across local, national, and international scales (see Mistry et al 2013aMistry et al , 2014a; Stage 3: Identifying practices for operationalizing ideal cross-scalar models for social-ecological survival, namely by identifying community survival strategies "best practices" (see Mistry et al 2013bMistry et al , 2016; and Stage 4: Building wider capacity and sharing, and applying "community survival strategies" best practice in other communities and civil society organizations (CSOs) (see Tschirhart et al 2014). …”
Section: Introductionmentioning
confidence: 99%